Incidence and risk factors of postoperative delirium in elderly surgical patients 2023 - Efrem Fenta; Diriba Teshome; Simegnew Kibret; Metages Hunie; Abebe Tiruneh; Amsalu Belete; Amsalu Molla; Belayneh Dessie; Kumlachew Geta (Scientific Reports)
Abstract Postoperative delirium has the potential to impact individuals of all age groups, with a significant emphasis on the elderly population. Its presence leads to an increase in surgical morbidity and mortality rates, as well as a notable prolongation of hospital stays. However, there is a lack of research regarding the prevalence, risk factors, and implications of postoperative delirium in developing nations like Ethiopia, which affects both patients and healthcare institutions. An observational study was conducted at hospitals in the South Gondar Zone to diagnose postoperative delirium in the Post-Anesthesia Care Unit (PACU) using the Nursing Delirium Screening Scale. Both bivariable and multivariable logistic regression techniques were employed to analyze the association between independent factors and postoperative delirium. The strength of the association was indicated by the odds ratio with a 95% confidence interval (CI). Any p-values below 0.05 were considered statistically significant. The incidence of postoperative delirium was determined to be 41%. In the multivariate logistic regression analysis, several factors were identified as significantly associated with postoperative delirium. These factors include an age of 75 or older (AOR, 11.24; 95% CI, 4.74–26.65), ASA-PS IV (AOR, 3.25; 95% CI, 1.81–5.85), severe functional impairment of activities of daily living (AOR, 3.29; 95% CI, 1.06–10.20), premedication with benzodiazepine (AOR, 4.61; 95% CI, 2.48–8.57), intraoperative estimated blood loss exceeding 1000 ml (AOR, 2.74; 95% CI, 1.50–4.98), and intraoperative ketamine use (AOR, 3.84; 95% CI, 2.21–6.68). Additionally, postoperative delirium was found to significantly prolong the duration of stay in the post-anesthesia care unit (PACU) and the length of hospital stay (p-value < 0.05). Patients aged 75 or older, ASA-PS IV, experiencing severe functional impairment of ADL, patients premedicated with benzodiazepine, patients with intraoperative estimated blood loss exceeding 1000 ml, and intraoperative ketamine use were identified as risk factors for post-operative delirium.